Real-world evidence of the effectiveness and utilization of subcutaneous C1INH long-term prophylaxis in patients with HAE in Spain and Germany - Maurer, Marcus; Cimbollek, Stefan; Kelly, Maebh; Rodney, Kyle; Elliott, John; LoboGuerrero, Eduardo; Magerl, Markus (Frontiers in Immunology, 2025)
Hereditary angioedema (HAE) types 1/2 are rare genetic disorders leading to C1 inhibitor (C1INH) deficiency/dysfunction. Guidelines recommend long-term prophylaxis (LTP) to prevent HAE attacks. Subcutaneous (SC) C1INH replacement therapy is approved for LTP in patients with HAE (age indication varies between countries). There is little real-world data on the outcomes of patients who switch to C1INH SC in Europe, particularly those who switch from C1INH IV. This retrospective patient chart analysis captured real-world evidence of the effectiveness of C1INH SC LTP in patients with HAE in Germany (n=69) and Spain (n=37). The primary endpoint was change in annualized attack rate (AAR) in patients who used C1INH IV LTP during a 6-month baseline period and switched to C1INH SC LTP for ≥6 months. Switching to C1INH SC LTP from C1INH IV LTP was associated with a 73.2% reduction in AAR (n=48; P<0.001) compared to baseline. Emergency Room (ER) visits and rescue medication use were also significantly reduced after switching to C1INH SC LTP from C1INH IV LTP. A similar reduction in AAR (68.9%), ER visits (49.8%), and rescue medication use (61.9%) was observed in the overall population (n=105), regardless of treatment at baseline. Similar changes from baseline were seen in patients from Germany and Spain.